The elite - Cass, Keira (New York : HarperCollins Publishers, 2013)
"Sixteen-year-old America Singer is one of only six girls still competing in the Selection--but before she can fight to win Prince Maxon and the Illean crown, she must decide where her own heart truly lies"-- Provided by publisher.
Keywords: Marriage--Fiction.; Contests--Fiction.; Social classes--Fiction.; Princes--Fiction.; Love--Fiction.; Revolutionaries--Fiction.